1997
DOI: 10.1007/s007050050174
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in the VP7 Gene of Human Rotavirus Serotype 3 (G3 Type) Isolated in China and Japan

Abstract: Sequence analysis of the VP7 gene was performed on twenty-one human isolates of serotype 3 related-rotavirus in China and Japan. The five Chinese isolates were found to be not similar to the 16 Japanese isolates and to SA11 (simian rotavirus). The Chinese isolates, especially CHW2 and CH-32, were different from the major serotype 3 human isolates. AU-1 and 02/92 which previously showed a wider spacing between RNA segments 10 and 11 by RNA polyacrylamide gel electrophoretic analysis, were more closely related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
32
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 18 publications
1
32
0
Order By: Relevance
“…A number of studies of VP7 of rotavirus clinical isolates belonging to the major serotypes (G-types) known to infect humans have indicated the existence of discrete genetic lineages of this protein (Jin et al, 1996 ;Wen et al, 1997 ;Maunula & von Bonsdorff, 1998 ;Piec & Palombo, 1999). Over the last decade, serotype G1 has represented the most common serotype responsible for the hospitalization of children worldwide (Gentsch et al, 1996).…”
mentioning
confidence: 99%
“…A number of studies of VP7 of rotavirus clinical isolates belonging to the major serotypes (G-types) known to infect humans have indicated the existence of discrete genetic lineages of this protein (Jin et al, 1996 ;Wen et al, 1997 ;Maunula & von Bonsdorff, 1998 ;Piec & Palombo, 1999). Over the last decade, serotype G1 has represented the most common serotype responsible for the hospitalization of children worldwide (Gentsch et al, 1996).…”
mentioning
confidence: 99%
“…Strains AU-1 and 02/92, which were previously shown to have a wider spacing between RNA segments 10 and 11 by RNA polyacrylamide gel electrophoretic analysis, were more closely related to each other and occupied a position distinct from the other Chinese and Japanese isolates in the phylogenetic tree (18). Thus, G3 rotaviruses were considered to be intraserotypically more heterogeneous than G 1, G2 and G4 viruses (8,18). From our G serotype sequence data, Suzuki et al reported that strains CH55 and CHW17, which were originally determined to be G3 by serological methods using monoclonal antibodies, did not make a single cluster with other G3 strains, but made a cluster with G1 strains (10), suggesting the occurrence of intragenic recombination in the VP7 gene between rotavirus strains bearing different serotypes.…”
mentioning
confidence: 83%
“…In our recent study on G3 human rotaviruses, the five Chinese isolates were found to be genetically distant from 16 Japanese isolates and SAll (18). Strains AU-1 and 02/92, which were previously shown to have a wider spacing between RNA segments 10 and 11 by RNA polyacrylamide gel electrophoretic analysis, were more closely related to each other and occupied a position distinct from the other Chinese and Japanese isolates in the phylogenetic tree (18). Thus, G3 rotaviruses were considered to be intraserotypically more heterogeneous than G 1, G2 and G4 viruses (8,18).…”
mentioning
confidence: 94%
See 2 more Smart Citations